Muhammadiyah’s Framework on The Community Economic Empowerment - Hakim, Imamul (Universitas Muhammadiyah Malang, 2018)
The contribution of Muhammadiyah in the field of economic empowerment in the community still does not seem real. The study of the concept of community economic empowerment based on religious, social organisations needs to be done to find a more effective approach. This study aims to examine the ideas or conceptual ideas of economic empowerment from Muhammadiyah Scholars and from Muhammadiyah Structural which have been written in the published form so that the meeting point can be found in an effective format of community economic empowerment. This study uses a library approach. The results in the research are grouped into two sources of economic empowerment concept ideas, namely; the concept from Muhammadiyah intellectuals and the concept from Structural Muhammadiyah. Firstly, from the perspective of Muhammadiyah scholars emphasising the full Structural involvement of Muhammadiyah in empowering the community's economy by fostering, mentoring and developing, building a network of entrepreneurs, business networks and distribution networks, played a role as a mediator between Muhammadiyah member entrepreneurs. Secondly, the concept of community economic empowerment in the perspective of Muhammadiyah Structural, there is not much difference with the first idea, but more emphasises the development of Muhammadiyah's Economic network and its members and focuses on economic empowerment at the branch level.